How can Rorty help nursing science in the development of a philosophical ‘foundation’? - Isaacs, Sandy (Nursing philosophy, 2009)
What can nurse scientists learn from Rorty in the development of a philosophical foundation? Indeed, Rorty in his 1989 text entitled Contingency, Irony, and Solidarity tantalizes the reader with debates of reason ‘against’ philosophizing. Forget truth seeking; move on to what matters. Rorty would rather the ‘high brow’ thinking go to those that do the work in order to make the effort useful. Nursing as an applied science, has something real that is worth looking at, and that nurse researchers need to think about. And as a profession built upon relationships, we should be thinking of the exchanges we have with those around us, of the contrasts in vocabularies used and of the contingencies involved, letting this launch us into our imaginings and areas of enquiry. The business of nurse researchers is to study what nurses do - how we care; Rorty would have us care. But, not to dismiss the reflective thinker as Rorty advocates for the self-doubting ironist to continue to seek the final vocabulary, the ideal of what ‘this’ means, accepting this as the best to be offered at the time. As a science struggling to find foundation, we need only to look at what we do and value - as antifoundational as Rorty portrays himself, Rorty ‘ironically’ may have revealed a foundation for nursing science that is consistent with its path.